Energy power lab for kids : 40 exciting experiments to explore, create, harness, and unleash energy - Hawbaker, Emily (Quarry, 2017)
"Energy Lab for Kids, created for kids by a teacher, offers challenging experiments and guided discussions along with how-tos, discoveries, and pointers from prize-winning kids."--